2017
DOI: 10.1111/jtxs.12259
|View full text |Cite
|
Sign up to set email alerts
|

The extrusion test and sensory perception revisited: Some comments on generality and the effect of measurement temperature

Abstract: We previously reported a high correlation between several sensory attributes and parameters from an extrusion test. The extrusion test showed the most robust correlation, and could be used to assess samples at both extremes of the texture range with respect to elasticity, for example, both samples that could not be extended as their very low elasticity led to their fracture during handling, as well as samples that could not be fractured in compression. Here, we reexamine the validity of the relations reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In the present study, a correspondence between the instrumental parameters of the texture and its sensory descriptors was observed. These correlations between the results of the sensory analysis and those of the instrumental tests were reported in previous studies about the textural modification of foodstuffs (Brenner et al, 2017;Conti-Silva et al, 2018;Sharma et al, 2017). The instrumental and sensorial firmness had the same behavior, and their values were higher in the adapted dishes than in their control dishes.…”
Section: Multivariate Analysissupporting
confidence: 85%
“…In the present study, a correspondence between the instrumental parameters of the texture and its sensory descriptors was observed. These correlations between the results of the sensory analysis and those of the instrumental tests were reported in previous studies about the textural modification of foodstuffs (Brenner et al, 2017;Conti-Silva et al, 2018;Sharma et al, 2017). The instrumental and sensorial firmness had the same behavior, and their values were higher in the adapted dishes than in their control dishes.…”
Section: Multivariate Analysissupporting
confidence: 85%
“…Since these results were obtained for a wide range of the texture from very brittle to very ductile, further development is expected. Brenner, Tomczynska-Mleko, Mleko & Nishinari 178) found that gelatin gels deviated from such a good fit obtained for polysaccharide gels at room temperature, and attributed it to the lower melting temperature of gelatin; the correlations, obtained using instrumental tests performed at a temperature far below body temperature, are not valid when the texture is strongly temperature-dependent over the temperature range covering the body and test temperatures. This is in line with ) who reported higher sweetness intensity or higher diffusion coefficient of sweeteners in gels with lower melting temperatures.…”
Section: Eating Difficultymentioning
confidence: 95%
“…Recently, the importance of taking into account the temperature effect has been reiterated in the extrusion test where a series of gels including gelatin with wide range of texture was examined (Brenner, Tomczynska-Mleko, Mleko, & Nishinari, 2017). This will be discussed later again.…”
Section: Tpa By Instrumental Compressionmentioning
confidence: 99%
“…Gelatin-based gels were perceived as less firm and less hard (Tomczynska-Mleko, Brenner, Nishinari, Mleko, & Kramek, 2014) than expected based on their mechanical properties compared to polysaccharide gels that have the same mechanical properties at room temperature but melt well above body temperature, underlying the importance of the measurement temperature for gels that melt during mastication (Brenner et al, 2017).…”
Section: Eating Difficulty and Extrusionmentioning
confidence: 99%